Friendship and social functioning following early institutional rearing: The role of ADHD symptoms. (October 2019) - Humphreys, Kathryn L.; Gabard-Durnam, Laurel; Goff, Bonnie; Telzer, Eva H.; Flannery, Jessica; Gee, Dylan G.; Park, Valentina; Lee, Steve S.; Tottenham, Nim
Abstract: Early institutional rearing is associated with increased risk for subsequent peer relationship difficulties, but the underlying mechanisms have not been identified. Friendship characteristics, social behaviors with peers, normed assessments of social problems, and social cue use were assessed in 142 children (mean age = 10.06, SD = 2.02; range 7–13 years), of whom 67 were previously institutionalized (PI), and 75 were raised by their biological families. Anxiety and attention-deficit/hyperactivity disorder (ADHD) symptoms, often elevated among PI children, were examined as potential mediators of PI status and baseline social functioning and longitudinal follow-ups (2 and 4 years later). Twenty-seven percent of PI children fell above the Child Behavior Checklist Social Problems cutoff. An examination of specific social behaviors with peers indicated that PI and comparison children did not differ in empathic concern or peer social approach, though parents were more likely to endorse aggression/overarousal as a reason that PI children might struggle with friendships. Comparison children outperformed PI children in computerized testing of social cue use learning. Finally, across these measures, social difficulties exhibited in the PI group were mediated by ADHD symptoms with predicted social problems assessed 4 years later. These findings show that, when PI children struggle with friendships, mechanisms involving attention and behavior regulation are likely contributors.